The Influence of Service Quality and Trust on Customer Satisfaction at Bank Bengkulu Talo Sub-Branch Office - Leoni Terry; Neri Susanti; Tito Irwanto (Journal of Accounting and Management, 2026)
This study aims to analyze the effect of service quality and trust on customer satisfaction at Bank Bengkulu Talos Branch Office. This research employed a quantitative approach using a survey method. The population consisted of all customers of Bank Bengkulu Talos Branch Office, with a sample of 100 respondents selected through purposive sampling technique. The research instrument was a questionnaire measured using a five-point Likert scale. The results of the validity and reliability tests indicated that all questionnaire items were valid and reliable. Data were analyzed using multiple linear regression with the assistance of SPSS software. The findings show that partially, service quality has a positive and significant effect on customer satisfaction. Trust also has a positive and significant effect on customer satisfaction. Simultaneously, service quality and trust significantly influence customer satisfaction. The coefficient of determination indicates that most of the variation in customer satisfaction can be explained by service quality and trust variables, while the remaining portion is influenced by other variables outside the research model. Therefore, improving service quality and strengthening customer trust are important strategies to enhance customer satisfaction and maintain long-term customer relationships.